2013
DOI: 10.5172/conu.2013.45.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Social and demographic determinants for breastfeeding in a rural, suburban and city area of South East China

Abstract: Breastfeeding is a traditional practice in China, yet few studies have explored its current trend after socioeconomic reform. This study aims to characterize breastfeeding rates and possible associations with sociodemographic factors using a breastfeeding questionnaire administered to 1,385 mothers of 6-year-old children. Rates were lowest among city residents and negatively associated with parental and grandmother education levels as well as mothers’ professional occupational status. These findings highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
(36 reference statements)
7
19
0
2
Order By: Relevance
“…The fathers' educational level was also an important factor for duration of breastfeeding discovered by the present study. This result supported by other studies [30,37]. It was observed that mothers who lived in Dhaka division breastfed for shorter period than other divisions in Bangladesh.…”
Section: Discussionsupporting
confidence: 87%
“…The fathers' educational level was also an important factor for duration of breastfeeding discovered by the present study. This result supported by other studies [30,37]. It was observed that mothers who lived in Dhaka division breastfed for shorter period than other divisions in Bangladesh.…”
Section: Discussionsupporting
confidence: 87%
“…According to this perspective and related literature [ 35 38 ], we propose that the low and middle income countries where the mothers emigrated from may be in the transformation phase (highest SES had lowest BF rate), whereas based on our results Taiwan is in the resurgence phase (highest SES had highest BF rate). Therefore, the diminished socioeconomic disparity among immigrant mothers could be due to their moving to a country in a later phase of breastfeeding transition where they may later undergo the process of transition from the transformation phase to the resurgence phase.…”
Section: Discussionsupporting
confidence: 65%
“…And United Nations International Children’s Emergency Fund reported that in 2014 the rate of exclusive breastfeeding among infants aged 6 months in China was only 28% with no increase in 3 years [ 20 ]. Multiple factors affected breastfeeding rates, including demographics, social support, socioeconomic status, parents’ educational backgrounds, and high cesarean section rates [ 21 , 22 ], etc. Meanwhile, many misconceptions about the breastfeeding still existed both in the general population and among healthcare professionals even in the neonatology department or NICU, such as the nutritional value of infant formula being the same as breast milk, breast milk not having any nutrition value after 10-month postpartum, and that DHM was not safe.…”
Section: Discussionmentioning
confidence: 99%